Lactic Acid Bacteria in Shellfish: Possibilities and Challenges - Einar Ringø (2020)
© 2019, © 2019 Taylor & Francis Group, LLC. Several investigations have investigated the gut microbiota in shellfish species, but less information is available on the favorable gut bacteria colonizing the GI tract, the lactic acid bacteria (LAB), and these studies have revealed the presence of Carnobacterium, Enterococcus, Lactobacillus, Lactococcus, Leuconostoc, Pediococcus, Streptococcus, Vagococcus, and Weissella. Identification of LAB in shellfish digestive tract are equally distributed between culture methods and culture-independent techniques. In the majority of the studies, the LAB are identified from the whole intestine or intestinal contents, while less studies have evaluated the autochthonous LAB. Some LAB isolated from shellfish are able to produce antibacterial substances towards different potential fish pathogenic bacteria. They also play an important role in improving the feed utilization and act as effective growth promoters in shellfish, and increase diseases resistance of shellfish culture against infectious bacteria and virus. In addition, enhancement of rearing water quality and increase the resistance against stressful condition have been recorded in shellfish fed LAB diets. LAB effects on the shellfish innate immune system are mostly studied in shrimp. In addition to LAB species studied in finfish or mammal systems, autochthonous strains of LAB are also used for studies. Generally, LAB-treated shellfish (crustaceans, mollusk, and Echinodermata) significantly improve innate immune parameters and display an increased survival rate from pathogen infections. Some of the studies indicate that the treatment of LAB mixture shows better immunomodulatory effects than that of a single strain of LAB. Studies of the underlying mechanisms of shellfish innate immune regulation are required for the identification of species-specific probiotics and the correct assessment of immunological effects. The present review paper focuses on recent findings in the field of isolation and detection of LAB in the GI tract of shellfish, some information on their presence in hepatopancreas and in muscle, their administration as probiotic, their mode of action, and their interaction with shellfish immune responses.